The utility of Islamic Financial Instruments in Preserving Nature - Muhammad Alan Nur; Sri Herianingrum (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
The degradation of nature is a global problem facing the world. The emergence of Green Finance is a response by the financial sector to preserve nature. The discussion related to Green Finance, which is linked to Islamic finance, is dominated by green Sukuk, because these instruments are currently in demand. Many other Islamic financial instruments can be explored to support Green Finance. This literature explores Islamic financial instruments that can be used to preserve nature. Reviews from various literary sources are used in this study to enrich the literature that explores the role of Islamic finance in preserving nature using various Islamic financial instruments. In addition to green Sukuk, the development of financing products carried out by Islamic financial institutions with the theme of Islamic green financing can contribute to preserving nature by providing services and financial access to environment-friendly projects. Islamic social finance instruments such as zakat, infaq, sadaqah, and waqf can also be developed to preserve nature and empower communities.